The Impact of the Renovation of Grassland on the Development of Segetal Weeds in Organic Farming - Eliza Gaweł; Mieczysław Grzelak; Bogusława Waliszewska; Magdalena Janyszek-Sołtysiak (Agriculture, 2022)
The intensive use or discontinuation of the use of swards can compromise biodiversity, yields, and feed quality; thus, leading to the degradation of permanent grasslands. Various methods of renovation are employed to restore the usability of degraded swards. In the years 2013–2016, a monofactorial field experiment was carried out on the Experimental Farm in Grabów (province of Mazowieckie, Poland). The experiment involved swards being reseeded after ploughing (P) and after disking with a compact harrow (H), with a non-renovated sward as the control treatment. The plots under renovation were reseeded with a lucerne–grass mixture. Both seedbed preparation methods for the renewed sward, ploughing (P) or shallow disking to a depth of 5 cm (H), were found to be effective for increasing sward yields, restricting weed growth, and reducing the number of weeds in the sward. The ploughing-based renovation method (P) had a strongly restrictive effect on biodiversity, as expressed by the H’ function value vis-à-vis the harrow method (H) and the non-renewed control (NR). Dicotyledonous species accounted for 92.3% of the weed population in the studied treatments. Of these, Taraxacum officinale, Achillea milefolium, Capsella bursa-pastoris, and Plantago maior occurred in the highest numbers.